English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Prove that <(n - )^2> = - ^2

2007-01-12 10:13:30 · 2 answers · asked by tedhyu 5 in Science & Mathematics Mathematics

2 answers

<> is expectation I take it. I like En better

E(n-En)^2
= E[n^2-2nEn+E^2n]
= En^2 -2En*En+E^2n
= En^2 -E^2n


En^2 means E(n^2)
E^2n means (En)^2

2007-01-12 10:20:19 · answer #1 · answered by Anonymous · 0 0

That's not much of a question. You really just need to expand the quadratic and use the properties of expectation to get the result. In particular, expectation is a linear operation:

E(aX) = aE(X)
and
E(X+Y) = E(X) + E(Y)

Go ahead, do it. Every statistics student must do this.

2007-01-12 18:22:47 · answer #2 · answered by modulo_function 7 · 0 0

fedest.com, questions and answers